(untitled) (Journal of the College of Basic Education, 2022)
The researcher’s tendency to use the strategy (Monroe and Slater) is to achieve the objectives of scientific conferences that sought to develop the educational process through the use of modern teaching methods that support thinking skills in general and critical thinking in particular, which has a positive impact on the intellectual growth of the learner and academic achievement. Therefore, the researcher raised the following question to determine the frameworks of the current research problem is: What impact does the use of the strategy of Monroe and Slater in the development of critical thinking skills? The research community means the vocabulary of all phenomena studied by the researcher and represented by all individuals and all persons who are the problem of research. (Anwar Waznaka, 2008: 306), therefore, the research community consisted of students of the Department of Art Education / College of Basic Education - University of Mustansiriya, who number (427) students distributed in (4) academic stages for the academic year 2018/2019. Since the subject of technical criticism and analysis in the curriculum of the third stage, therefore, the students were selected for the purpose of providing the safety of experimental design, where the number of members of this stage (62) students distributed in two classrooms (32) students in the Division (A) and (30) students in Division (B), the researcher used a set of statistical methods to reach the results of the research, the most important of which are: The students of the experimental group that studied critical thinking skills using the Monroe and Slater strategy according to the content prepared in the teaching plans and measured according to the post-test prepared for this purpose, are superior to those of the students of the control group. Through the clarity of the educational and behavioral goals with cognitive and skill-based performance that facilitated students to learn critical thinking skills. The main conclusions are: The components of the strategy of Monroe and Slater (conclusion - assumptions or assumptions - deduction - interpretation - evaluation of arguments) in the development of critical thinking skills among students of the experimental group of subjects taught according to the teaching plans, making it a purposeful and self-directed and collective process.